2018
DOI: 10.1007/s10880-018-9552-0
|View full text |Cite
|
Sign up to set email alerts
|

Illness Identity in Adults with a Chronic Illness

Abstract: The present study examines the concept of illness identity, the degree to which a chronic illness is integrated into one's identity, in adults with a chronic illness by validating a new self-report questionnaire, the Illness Identity Questionnaire (IIQ). Self-report questionnaires on illness identity, psychological, and physical functioning were assessed in two samples: adults with congenital heart disease (22-78 year old; n = 276) and with multisystem connective tissue disorders (systemic lupus erythematosus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
150
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(213 citation statements)
references
References 57 publications
17
150
1
Order By: Relevance
“…However, it is also possible that a more complex underlying mechanism is present. Indeed, a prior study has shown that patients who felt engulfed by their condition reported more depressive and anxiety symptoms . Such symptoms, in turn, are risk factors for higher healthcare use in adults with CHD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also possible that a more complex underlying mechanism is present. Indeed, a prior study has shown that patients who felt engulfed by their condition reported more depressive and anxiety symptoms . Such symptoms, in turn, are risk factors for higher healthcare use in adults with CHD .…”
Section: Discussionmentioning
confidence: 99%
“…Sample items for the different subscales are, respectively, “I just avoid thinking about my illness,” “Because of my illness, I have become a stronger person,” “I am able to place my illness in my life,” and “My illness completely consumes me.” A mean score was calculated per subscale. A prior study, performed on data from T 2013 of the Belgian branch of APPROACH‐IS, demonstrated that the IIQ is valid and reliable to be used in adults with CHD . More specifically, exploratory and confirmatory factor analysis indicated that IIQ subscale scores could differentiate among the 4 intended illness identity states in patients with CHD and multisystem connective tissue disorders (ie, factorial validity).…”
Section: Methodsmentioning
confidence: 99%
“…Socio‐demographic data were collected by self‐reports and information on medical history was retrieved by chart reviews. Details on the methodology of APPROACH‐IS have been provided in a methods paper , and numerous papers have described findings obtained from this global sample or from patients from specific countries or regions .…”
Section: Approach‐ismentioning
confidence: 99%
“…To date, differences in psychological functioning could not be sufficiently explained by the underlying severity of disease in ACHD [11]. Apparently, some patients succeed in overcoming disease-related challenges, while others experience substantial difficulties that lead to increased emotional distress.…”
Section: Introductionmentioning
confidence: 99%